2008
DOI: 10.1080/07315724.2008.10719683
|View full text |Cite
|
Sign up to set email alerts
|

The Baseline Serum Lipoprotein Profile Is Related to Plant Stanol Induced Changes in Serum Lipoprotein Cholesterol and Triacylglycerol Concentrations

Abstract: People with an unfavorable serum lipid and lipoprotein profile benefit even more of plant stanols than people with a more favorable profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 37 publications
8
57
1
3
Order By: Relevance
“…Besides their cholesterol-lowering properties, plant sterols/stanols are also able to reduce triglyceride levels ( 8,9 ). In our study, we observed that plant sterol and stanol feeding pro-infl ammatory genes ( Table 4 ) suggesting that the observed effect of PSE and PSA on hepatic VLDL production occurred independent of potential anti-infl ammatory effects of these compounds.…”
Section: Discussionsupporting
confidence: 48%
“…Besides their cholesterol-lowering properties, plant sterols/stanols are also able to reduce triglyceride levels ( 8,9 ). In our study, we observed that plant sterol and stanol feeding pro-infl ammatory genes ( Table 4 ) suggesting that the observed effect of PSE and PSA on hepatic VLDL production occurred independent of potential anti-infl ammatory effects of these compounds.…”
Section: Discussionsupporting
confidence: 48%
“…Al igual que otros autores (31,32), hemos analizado si la eficacia de los EV es dependiente de los niveles basales de los sujetos, encontrando mayor descenso de LDL-c cuanto mayor es el nivel basal al inicio del tratamiento.…”
Section: Discussionunclassified
“…Some studies suggest that phytosterols may decrease serum triglycerides in subjects with high serum concentrations of triglycerides. 79,80 Nevertheless, the general consensus is that phytosterol therapy is most effective for lowering LDL cholesterol with maximum efficacy at approximately 3 g/d. 75,76,81 Demonty et al 81 recently developed a continuous dose-response equation using 141 trial arms (from 84 studies) and concluded that a dose of 3 g/d lowers LDL cholesterol 11%, whereas a dose of 2 g/d lowers LDL cholesterol 9%.…”
Section: Phytosterol Efficacy Dose and Dose Frequencymentioning
confidence: 99%
“…Some studies have reported a significant correlation between baseline LDL cholesterol concentration and the magnitude of change, 88,89 whereas others have not. [90][91][92] Using a systematic approach, Naumann and coworkers 79 analyzed data from five studies conducted in their laboratory and concluded that phytosterol consumption resulted in larger absolute decreases in LDL cholesterol when patients had higher baseline serum levels, but the percent decrease was not affected. A recent meta-analysis of 141 trial arms also supported the conclusion that absolute (but not relative) changes in LDL cholesterol are significantly correlated with baseline LDL cholesterol concentration, thus indicating that phytosterol therapy in individuals with higher baseline LDL levels have greater absolute reductions in LDL cholesterol.…”
Section: Effect Of Baseline Serum Cholesterolmentioning
confidence: 99%